Knowledge, attitude and practice of vectors and vector-borne diseases with special reference to dengue at metropolitan Chennai, Tamil Nadu, India - Sakthivadivel, Murugesan; Mukhilan, Rajaratnam Rajiv; Jeevitha, Ganesan; Sakthivadivel, Jeyabharathi; Narayanan, Kirubakaran; Tennyson, Samuel (International Journal Of Community Medicine And Public Health, 2020)
Background: Infectious diseases transmitted by insects and other animal vectors have long been associated with significant human illness and death. Methods: The study design was a descriptive cross-sectional study concerning knowledge, attitude and practices about mosquito breeding sources, mosquito density period, mosquito spreading diseases, protection from mosquito bites, awareness on vector-borne diseases, usage of chemical and natural products among the people in selected areas of metropolitan Chennai by accurate random sampling covering one thousand respondents based on age group, education and gender. Results: The overall respondents were analyzed about the breeding sources and it was found that water (40%) was its main source. In average, the majority of respondent’s observation (57%) on mosquito breeding season was during monsoon. In overview of the public health concern, majority (54%) of the people answered that they had been infected with mosquito-borne diseases. The results also indicated that the respondents of the study area used liquidator (40%), coil (31%), repellent cream (9%) and indoor spraying repellents (17%) to protect themselves from mosquito bites. In response to the knowledge on herbal products, 54% of the respondents were aware about it. Conclusions: The study documented that majority of respondents were unaware rather than knowing the facts with regard to mosquito-borne diseases and its details. Therefore, from the present survey, it can be stated that KAP surveys access communication processes and sources that are key to defining effective activities and messages in vector-borne diseases prevention and control.